2021
DOI: 10.1007/s40899-021-00576-y
|View full text |Cite
|
Sign up to set email alerts
|

Physical–chemical evaluation of groundwater quality in semi-arid areas: case study—Sabzevar plain, Iran

Abstract: Groundwater is one of the most important water sources in arid and semi-arid areas. With the increasing world population and the water demand for agriculture and urban use, the need for water resources has increased, especially in arid and semi-arid regions, where groundwater resources play a significant role. To prevent the pollution of groundwater resources, various studies for their preservation and maintenance should be carried out, including a detailed plan for proper management of water resources and est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 34 publications
(39 reference statements)
0
6
0
Order By: Relevance
“…9). diagram (1977) is the most popular method to classify the suitability of drinking water quality (Alavi et al 2016, Almodaresi et al 2019, Panahi et al 2021). The diagram is based on the concentration of major cations (Ca 2+ , Mg 2+ , Na + ), anions (Cl − , HCO 3− , SO 4 2+ ), total dissolved solids (TDS) and total hardness (TH).…”
Section: Water Quality Indexmentioning
confidence: 99%
“…9). diagram (1977) is the most popular method to classify the suitability of drinking water quality (Alavi et al 2016, Almodaresi et al 2019, Panahi et al 2021). The diagram is based on the concentration of major cations (Ca 2+ , Mg 2+ , Na + ), anions (Cl − , HCO 3− , SO 4 2+ ), total dissolved solids (TDS) and total hardness (TH).…”
Section: Water Quality Indexmentioning
confidence: 99%
“…In dry and semi-arid areas, groundwater is one of the most important sources of water. Due the expanding worldwide population and growing demands for water for both urban and agriculture uses [6]. For millions of people in poor nations, groundwater is considered as a unique source of safe drinking water [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Research has indicated that in rural areas, the leakage of agricultural fertilizers and the discharge of livestock manure are the primary contributors to nitrate pollution [7][8][9]. However, in urban areas, with the growth of urban populations, the main sources of nitrate pollution have shifted to domestic sewage discharge and landfill leakage [10][11][12][13]. Compared to deep groundwater, nitrate pollution in shallow groundwater is more common and has been studied more [14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Among the numerous studies on nitrate pollution in groundwater, hydrochemical, isotopic, and multivariate statistical methods are the most commonly used methods [7,26,27,31,32]. However, these studies mostly focus on cities located in plains, and there is a lack of research on cities located in river valleys [12,14,19].…”
Section: Introductionmentioning
confidence: 99%